The Deoband madrassah movement countercultural trends and tendencies - Moj, Muhammad (London [u.a.] Anthem Press, 2015)
The Deoband madrassah movement (DMM): research context -- Origin of the DMM: seeds of a counterculture -- The DMM in united India: activist countercultural trends -- The DMM in Pakistan: countercultural politics and extremism -- Deobandi Islam: countering folk Islam and popular custom -- The DMM versus mainstream society: viewpoints of Deobandi journals and students
The Deoband madrassah movement (DMM): research contextOrigin of the DMM: seeds of a counterculture -- The DMM in united India: activist countercultural trends -- The DMM in Pakistan: countercultural politics and extremism -- Deobandi Islam: countering folk Islam and popular custom -- The DMM versus mainstream society: viewpoints of Deobandi journals and students.
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Islam and politics -- Pakistan; Islamic Religious Education -- Pakistan; Islamic fundamentalism -- Pakistan; Islam and politics -- Pakistan; Islamic Religious Education -- Pakistan; Islamic fundamentalism -- Pakistan; Deoband School (Islam)